Uso del Cloro en las Líneas de Empacado de Productos Cosechados Frescos - Mark A. Ritenour; Steven A. Sargent; Jerry A. Bartz; Elena E. Lon Kan (EDIS)
HS-1082, a 5-page article by M.A. Ritenour, S.A. Sargent, J.A. Bartz, and E.E. Lon Kan, is the Spanish language version of HS-761, Chlorine Use in Produce Packing Lines. It outlines principles for effectively using chlorine for water sanitation including sections on forms of chlorine, factors influencing chlorine activity, how to maintain adequate chlorine concentrations, test kits, recommendations, and how to mix chlorine solutions. Published by the UF Department of Horticultural Sciences, February 2007.